1997
DOI: 10.1093/gerona/52a.3.m142
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Nurse Aides' Functional Health Assessments of Nursing Home Residents

Abstract: Nurse aides can accurately use well-calibrated instruments to assess nursing home residents' functional health. Demonstration of assessment accuracy in nurse aides, who provide the majority of direct care for nursing home residents, documented a valuable clinical resource for planning and evaluating resident care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…). Similarly, perceived quality of care is strongly correlated with patient satisfaction (e.g., Sikorska‐Simmons ) and previous research has found that frontline worker assessments of patient health are as accurate as those of mid‐level practitioners (Hartig, Engle, and Graney ; Engle, Graney, and Chan ).…”
Section: Introductionmentioning
confidence: 85%
“…). Similarly, perceived quality of care is strongly correlated with patient satisfaction (e.g., Sikorska‐Simmons ) and previous research has found that frontline worker assessments of patient health are as accurate as those of mid‐level practitioners (Hartig, Engle, and Graney ; Engle, Graney, and Chan ).…”
Section: Introductionmentioning
confidence: 85%
“…Another limitation in the study was that the Barthel index was based on verbal report from the DCWs rather than doing direct observation of the resident by the research team. Although DCWs have demonstrated accurate, nonbiased assessment of functional status in other research, 18,22 it is possible that our results may have been biased by the views of the DCWs. We did not specifically evaluate residents for adequate vision or hearing, and thus their performance may have been influenced by sensory changes.…”
Section: Limitationsmentioning
confidence: 77%
“…SOC data were obtained by interviewing the nursing assistant who cared for and observed the resident's functional performance the day of data collection. Nursing assistants were chosen to provide SOC data because they were the direct care givers and because research has shown that nursing assistants can accurately assess residents’ function 18 …”
Section: Methodsmentioning
confidence: 99%